Halal Tourism Policy in the Southeast Asian Countries - Ali Muhyidin; Muhammad Imam; Donni Edwin; Amri Yusra (Soshum: Jurnal Sosial dan Humaniora, 2025)
Economic growth and global population expansion have created significant opportunities for the halal tourism industry. As home to the world's largest Muslim population, Southeast Asia is positioning itself as a key destination for halal tourism. This study examines the strategies employed by Indonesia, Malaysia, Singapore, and Thailand to enhance their competitiveness in the regional and global halal tourism market. Using a comparative qualitative approach and secondary data analysis, the research finds that Indonesia leverages its cultural diversity and rich tourist attractions, while Malaysia focuses on attracting Middle Eastern tourists through targeted marketing. Despite having a smaller Muslim population, Singapore capitalizes on its strategic location, and Thailand adapts through strong government support. The findings underscore the importance of internal and institutional factors in strengthening each country's appeal as a halal tourism destination.